Ultra-Wideband Robust RCS Reduction with Triangle-type AMC Structure - Song, Tao; Cong, Lili; Tong, Chuangming (Společnost pro radioelektronické inženýrství, 2018)
A novel planar artificial magnetic conductor (AMC) structure is presented for ultra-wideband radar cross section reduction (RCSR). The structure consists of three different AMC tiles in a quadruple triangle-type chessboard configuration. By precise design, a 180°±30° reflection phase difference between every two of the three units nearly covers from 3.98GHz to 18.84GHz to broaden the RCSR bandwidth. By this means, the scattered energy is redirected into several lobes and the measured RCSR for over -6dB is achieved nearly from 3.62GHz to 18GHz with a relative bandwidth of 133.02% for both polarizations. Both full-wave simulation and measurement results verify the capability and potentiality of the proposed design for ultra-wideband RCSR.
Keywords: Ultra-wideband; artificial magnetic conductor; polarization independent; radar cross section reduction; quadruple triangle chessboard